Non-fragile asynchronous event-triggered control for uncertain delayed switched neural networks. (August 2018) - Luo, Jinnan; Tian, Wenhong; Zhong, Shouming; Shi, Kaibo; Wang, Wenqin
Abstract: This study constructs and investigates the non-fragile asynchronous event-triggered control for uncertain switched neural networks with communication delays and Bernoulli distribution. The system involves both the randomly occurring uncertainties of all parameters (ROUAPs) in the switched system model and randomly gain perturbations of the controller. By introducing several stochastic variables, a new model structure obeying Bernoulli distribution is formulated to describe the uncertainties of system and the controller. In addition, an improved non-fragile asynchronous event-triggered control scheme is proposed and a modified Lyapunov–Krasovskii function (LKF) is chosen via flexible terminal method (FTM) to deal with such uncertain switched systems with delays. By combining newly bounding inequalities and convex combination method, new results are presented for the uncertain delayed switched error systems in terms of linear matrix inequality (LMI). Furthermore, the non-fragile asynchronous event-triggered controller is designed with less communication burden. Finally, a numerical example is provided to verify the merits of the proposed results.